2021
DOI: 10.1108/ejm-02-2019-0125
|View full text |Cite
|
Sign up to set email alerts
|

Gender stereotypes in advertising have negative cross-gender effects

Abstract: Purpose This paper aims to investigate cross-gender effects of gender stereotypes in advertising. More specifically, it proposes that the negative effects found in studies of women’s reactions to stereotyped female portrayals should hold across gender portrayal and target audience gender. Design/methodology/approach In two experimental studies, the effects of stereotyped portrayals (vs non-stereotyped portrayals) across gender are compared. Findings The results show that advertising portrayals of women and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 108 publications
(212 reference statements)
0
34
0
3
Order By: Relevance
“…It has been suggested that female stereotypes in general, and particularly sexual stereotypes, have harmful societal effects. Our finding that CS procedures increase perceptions of sexually oriented beauty suggests negative effects for society in general but may also lead to negative effects for the advertising resulting from ethical considerations by consumers (Åkestam et al, 2021; Middleton et al, 2020). The occurrence of a natural beauty type in our study suggests conducting consecutive research to assess the reactions of consumers in Thailand to Dove campaigns that promote natural beauty.…”
Section: Concluding Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…It has been suggested that female stereotypes in general, and particularly sexual stereotypes, have harmful societal effects. Our finding that CS procedures increase perceptions of sexually oriented beauty suggests negative effects for society in general but may also lead to negative effects for the advertising resulting from ethical considerations by consumers (Åkestam et al, 2021; Middleton et al, 2020). The occurrence of a natural beauty type in our study suggests conducting consecutive research to assess the reactions of consumers in Thailand to Dove campaigns that promote natural beauty.…”
Section: Concluding Discussionmentioning
confidence: 80%
“…The reported findings are relevant for the literature addressing the stereotypical portrayal of women in firm’s commercial messages (e.g. Åkestam et al, 2021; Middleton et al, 2020). It has been suggested that female stereotypes in general, and particularly sexual stereotypes, have harmful societal effects.…”
Section: Concluding Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…The immediate recognition of certain stereotypes means they are widely used in the production of effective advertising and in sitcoms (Bauer et al. , 2018; Åkestam et al. , 2021).…”
Section: The Logic Of Psc Theory For the Control Of Stereotypesmentioning
confidence: 99%
“…The stronger the stereotype, the more incisive its effects will be, and the longer they are likely to last. The immediate recognition of certain stereotypes means they are widely used in the production of effective advertising and in sitcoms (Bauer et al, 2018;Akestam et al, 2021).…”
Section: The Logic Of Psc Theory For the Control Of Stereotypesmentioning
confidence: 99%